Memahami Konflik Keluarga melalui Pendekatan Sosiologi Hukum Islam (Studi Lapangan di Pengadilan Agama Kota Kediri) - Ach. Khiarul Waro Wardani (Institut Agama Islam Negeri (IAIN) Kediri, 2022)
Socially, the family is the smallest community in society which is formed through a legal engagement (marriage), as well as according to Islamic law. With the formation of a family, what inevitably happens is the emergence of family conflicts which can arise from internal (family) and can also be external (outside parties) as happened in the City of Kediri, with as many as 325 cases of family conflicts that ended in lawsuits for divorce or divorce only in a relatively short period of time, namely the last 6 months in 2022. Understanding the conflicts that occur in the family aims to avoid the general societal stigma that conflict is something negative, even though there are positive things from conflict if you take lessons from conflict such as being aware of each other's shortcomings and being able to open to each other. Therefore, according to the author, the Sociology of Islamic Law is the right approach to use in understanding conflict in the family. By understanding the Sociology of Islamic Law, the rules for fostering a family will be understood by every member of the family, such as the rules that Allah SWT stipulates in QS. A-Rum: 21, QS. At-Tahrim: 6 and so on. The method used in this study uses a qualitative research approach the type used in this research is a type of field research or field, it can also be said as empirical or sociological research. In conclusion, as far as we all know, the stigma of conflict is something bad, of course, this is not the case if we look at it from the other side (social and Islamic law). An understanding of life, namely sociology, and Islamic law to resolve all family conflicts is the most important part to be known together to realize dreams in the family, namely sakinah mawaddah warohmah.